Host response to respiratory syncytial virus infection - Arruvito, Maria Lourdes (2015)
Purpose of review: Respiratory syncytial virus (RSV) infection is the leading cause of bronchiolitis and hospitalization in young infants and causes 100 000–200 000 deaths annually. There is still no licensed vaccine against RSV infection and the therapeutic options are mainly supportive. Despite almost six decades of research, important knowledge gaps remain with respect to the characterization of immune mechanisms responsible for protection and pathogenesis, as well as to the identification of risk factors that predict the severity of infection. Recent findings: Observations made in mouse models and young children suggest that the early innate immune response plays a major role in the pathogenesis of bronchiolitis due to RSV infection. Recent studies have improved our understanding of the role of the adaptive immune response mediated by TH1, TH2, TH17, regulatory T cells, and CD8þ T cells in the pathogenesis and resolution of RSV infection. Moreover, investigations performed in the last years have made important contributions to our knowledge of the immune response in young children, the principal risk group for severe disease. Summary: A comprehensive understanding of how the protective and deleterious immune response during the course of RSV infection is induced in young children remains a challenge over the coming years.